Staurogyne nitida, a new combination among Brazilian Acanthaceae - Braz, Denise Monte; Daniel, Thomas F. (Phytotaxa, 2018)
Staurogyne carvalhoi is a later heterotypic synonym of Ebermaiera nitida. The new combination Staurogyne nitida, based on the older name, is herewith proposed.